Research status of triglyceride glucose-body mass index (TyG-BMI index) - Song, Ke; Xu, Yuwan; Wu, Shuairan; Zhang, Xiaojie; Wang, Yi; Pan, Sancong (Frontiers in Cardiovascular Medicine, 2025)
Insulin resistance (IR) represents a pivotal metabolic risk factor, with metabolic abnormalities intricately linked to increased predisposition to cardiovascular, digestive, and immune system disorders. While the triglyceride glucose (TyG) index is widely recognized as a simple and specific surrogate marker for IR, the triglyceride glucose body mass index (TyG-BMI), incorporating obesity metrics, has emerged as a more robust predictor of IR. Growing evidence underscores the strong association between TyG-BMI index and multisystem diseases that span cardiovascular, metabolic, and neoplastic pathways. Monitoring TyG-BMI index enables proactive management of lifestyle modifications, dietary interventions, and physical health strategies, thereby reducing disease prevalence. This review synthesizes the pathophysiological mechanisms underlying TyG-BMI, alongside its clinical utility and cutting-edge research advancements in hypertension, coronary artery disease, stroke, diabetes, non-alcoholic fatty liver disease, hyperuricemia, and cancer. Particular emphasis is placed on the role of TyG-BMI index in influencing disease progression, highlighting its potential as a transformative biomarker for risk stratification and therapeutic targeting across diverse medical disciplines.